IMPLEMENTATION OF WEBSITE PERFORMANCE EVALUATION WITH SIMILARWEB ON ACADEMIC WEBSITES - Ika Oktavia Suzanti; Fifin Ayu Mufarroha; Khusnul Fatimah; Doni Abdul Fatah; Hanifudin Sukri; Achmad Dafid (Jurnal Simantec, 2022)
Trunojoyo University Madura is a state university in Indonesia. The Trunojoyo Madura University website is used for information delivery media. The website can be accessed by anyone and used to make announcements for both students and outsiders. Based on this, the desired website quality must have high performance, usability, mobile friendliness, accessibility, SEO (Search Engine Optimization), connected to social media, and safe. This study was conducted to determine the level of usability through evaluating the performance of the academic website of Trunojoyo Madura University. Therefore, this study evaluates the performance of the website by using an automatic evaluation tool, namely SimilarWeb. This tool checks the level of popularity of a website both in terms of ranking and the number of visitors who access the website. In addition, measurements from the usability side were taken to determine the usability of the website obtained from the responses of students and visitors who have accessed the website. The results showed that by using SimilarWeb website traffic was obtained at a good level. Usability measurement has been carried out, as many as 58 respondents have answered 15 questions.